Improvement of thua nao production using protein-rich soybean and Bacillus subtilis TN51 starter culture - Katekan Dajanta (2018)
Thua nao, a Thai traditional fermented soybean, is locally produced, of irregular quality and under risk of contamination with spoilage and pathogenic microorganisms during the artisanal process. This study aims to select a protein-rich soybean variety as a material for thua nao fermentation and improve organoleptical quality of the product by fermenting sterilized soybean with pure starter of Bacillus subtilis TN51 previously isolated from a traditional thua nao. Changes in microbiological and physicochemical qualities of soybean were monitored through fermentation period for 72 h. The completely fermented products were also subjected to sensory evaluation and antimicrobial activity against 13 microbial pathogens and two fermentative yeasts. Of five soybean cultivars tested (i.e., CM60, Pabong7, Kunpae, TG55 and TG145), based on seed size, production yield, protein and fat contents, TG145 was the most suitable for production of thua nao due to its high protein content (45.8%), lowest fat (15.6%), small seed size (11.1 g/100 seeds) and potent production yield (358 kg/rai). Thua nao produced by fermented autoclaved soybean with pure starter culture of B. subtilis TN51 (TNB51) could be improved considerably for its microbiological and chemical qualities, especially using a smaller amount of ammonia that led to a more organoleptically acceptable product than thua nao produced by naturally occurring microbial fermentation (TNMX). Of tested microorganisms, only Gram-positive bacteria (i.e., Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus luteus, Bacillus cereus, and Listeria monocytogenes) were inhibited by thua nao methanolic extracts. © Springer-Verlag and the University of Milan 2011.